Work-Life Balance in the Islamic Perspective: A Study of Qur’anic Exegesis (Tafsir) and Hadith on the Balance Between Worldly Life and the Hereafter - Anzari, Agung; Zaen, Ibrahim Putra; Alamsyah, Reyga; Firdaus, Ryouta Agil; Abdussalam, Muhammad Haidar; Habibi, Maulana Fatahillah; Kurniawan, Taufiq (Penerbit Yayasan Daarul Huda Kruengmane, 2026)
This study aims to examine the concept of work-life balance from an Islamic perspective through an analysis of Qur’anic exegesis and Hadith that discuss the balance between worldly life and the hereafter. The research employs a library research method by examining relevant verses of the Qur’an and Hadith related to work, worship, and social responsibility through classical and contemporary tafsir and Hadith literature. The findings indicate that Islam views balance in life as an essential principle, in which work is considered a form of worship as long as it is carried out responsibly and does not neglect spiritual and social obligations. The balance between worldly and spiritual life is reflected in the principle of moderation (wasathiyah), which guides Muslims to live their lives in a proportional manner. In conclusion, the concept of work-life balance in Islam is grounded in the teachings of balance between worldly life and the hereafter as found in the Qur’an and Hadith.